Critical Condition of Sensorless Induction Generator Using Flux Weakening in Wind Turbine Application - Nanda Avianto Wicaksono; Abdul Halim; Aries Subiantoro; Feri Yusivar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper was intended to examine thoroughly a critical condition of the sensorless induction generator using flux weakening in wind turbine application. The critical condition would happen when the rotor speed reached the critical rotor speed reference. The critical rotor speed reference was the highest of the rotor speed reference that still caused the stable response. It was obtained by increasing the rotor speed reference until the system response became unstable. In the low speed range of wind showed that there was no unstable condition whatever a rotor speed reference was set. On the other hand, there was a critical rotor speed reference in the medium and high speed range of wind. The unstable condition was caused by the induction generator that received a power higher than its capacity, so its rotor speed couldn't be maintained at reference value. The first solution was suggested that the stable condition would be made by setting the rotor speed reference at the minimum critical reference. The second solution was suggested that the controlling rotor speed in triangle area between the critical condition and the operation that used the minimum critical reference for the rotor speed reference. In the triangle area, the rotor speed was controlled by setting the tip speed ratio.